Appointment and Conduction of Examinations: Legislative and Practical Problems (Bulletin of Kharkiv National University of Internal Affairs, 2019)
It has been noted that the problems of procedural guaranteeing of the rights of victims, suspects (accused) in terms of reforming the criminal procedural legislation are relevant during the appointment and holding of the examination and require further research.The aim of this study is to analyze the current criminal procedural legislation on the appointment and conduction of examination and to develop propositions for its improvement.The authors of the article have analyzed the existing procedural legislation on the appointment and conduction of examination; have defined the problematic issues of procedural guaranteeing of the rights of victims, suspects (accused) in the appointment and conduction of examination; and have offered the ways to solve them; have substantiated the need for legislative regulation of additional and re-examination of explosive and technical examination and have provided forensic recommendations to eliminate these problems.Based on the conducted research, the authors have provided the following suggestions and recommendations:1) to enshrine the right of the prosecution and defense parties in the Art. 243 of the Criminal Procedural Code of Ukraine (CPC) to independently appoint an examination;2) to declare it appropriate to supplement Section 3 of the CPC with the Art. 56-1 “Rights of the victim in the appointment and conduction of examination”, which should enshrine the relevant rights;3) to declare it expedient to supplement Section 20 of the CPC of Ukraine with the Art. 242-1, which should determine the rights of the suspect (accused) in the appointment and conduction of examination;4) to standardize the procedure for the appointment of additional expertise in paragraph 11 of the Art. 101 of the CPC;5) to standardize the procedure for the appointment of re-examination in paragraph 12 of the Art. 101 of the CPC;6) to recommend investigators and judges to determine the expert’s questions depending on the objects of expert examination;7) to improve the stage of experimental testing of objects in carrying out explosive examination.
Keywords: examination; a victim; a suspect; additional examination; re-examination; explosive examination.